Point-to-point transportation analysis for domestic travel in Malaysia - Romli, Fairuz Izzuddin; Rashid, H. (CRC Press, 2015)
Point-to-point travel refers to the trip taken from the initial departure point to the final destination point, which can be further categorized as either direct or non-direct. Direct point-to-point travel indicates that the trip is made with a single transportation mode from beginning until the person reaches the final destination. On the other hand, the non-direct type of point-to-point travel involves several modes of transportation throughout the journey. Comparison analysis is made between the avail-able modes of domestic transportation such as buses, trains, commercial flights and cars to determine the preference and the market potential for direct point-to-point travel means. Several evaluation criteria including time on transport, time of waiting, cost of transport, cost of other expenses, travel comfort, flexibility of departure point and privacy are used in this study. Based on the result from case studies of domestic travel in Malaysia, it shows that direct point-to-point means of transportation represented by cars generally have higher benefits in comparison to other means of transportation, especially in terms of time and travel costs. This signifies a big potential in introducing a better means of direct point-to-point transportation than current cars like the dual-mode Personal Air Vehicle (PAVE) for domestic travel in Malaysia